Nutritional prospect of aphrodisiac blend from Cyprus esculentus, phoenix dactylifera, and Zingiber officinal in modulating sexual functions - Muhammed Maikarfi (International Journal of Food Sciences and Nutrition Innovations, 2025)
Background of Study: Sexual dysfunction is a multifactorial condition that can be influenced by micronutrient status. In Nigeria, locally prepared beverages are widely consumed as aphrodisiacs to enhance libido, erectile function, sperm quality, and fertility, yet combined formulations remain poorly studied. This study aimed to evaluate the nutritional composition of a powdered beverage blend made from dried tiger nut, date, and ginger in a 50:40:10 ratio, and to examine literature-based evidence on the effects of its components on sexual function.Aim and Scope of Study: The blend was analyzed for proximate composition, vitamin content, and mineral levels using standard analytical methods. Relevant peer-reviewed studies were also reviewed to identify the biological roles of the blend’s components in sexual and reproductive health. Data were analyzed using descriptive statistics, independent t-tests, and one-way ANOVA at p ≤ 0.05.Results: Results showed that the beverage was rich in carbohydrates (76.20%), dietary fiber (7.17%), and fat (9.67%), with low moisture content. It contained appreciable levels of essential minerals, including magnesium, zinc, selenium, copper, and manganese, as well as vitamins A, B₆, B₉, B₁₂, and C. Literature evidence indicated that tiger nut, date, and ginger contribute to sexual function through modulation of hormonal activity, gene expression, spermatogenesis, and erectile mechanisms.Conclusion: In conclusion, the tiger nut–date–ginger beverage possesses a favorable nutrient profile that supports reproductive physiology. While the findings suggest its potential as a nutritional adjunct for improving sexual function, further experimental and clinical studies are needed to validate its efficacy and safety.